2018
DOI: 10.1111/dmcn.13757
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fibre layer thinning is associated with worse visual outcome after optic neuritis in children with a relapsing demyelinating syndrome

Abstract: Long-term visual impairment is reported in 40% of children with a relapsing demyelinating syndrome following optic neuritis. Relapse of optic neuritis, occurring more frequently in the non-multiple-sclerosis group. Retinal nerve fibre layer thinning is associated with worse visual outcome. Optical coherence tomography can be used alongside clinical parameters as an objective measure of neuroretinal loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…Of these, 202 articles were selected and assessed for eligibility at the full-text level. After careful evaluation, 35 studies were included that met the inclusion criteria ( 8 , 29 , 30 , 33 , 36 , 39 , 41 , 45 , 47 , 48 , 51 – 54 , 57 , 59 , 63 , 65 , 66 , 68 , 69 , 71 , 72 , 74 85 ). The detailed flow chart is presented in Supplementary Figure 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 202 articles were selected and assessed for eligibility at the full-text level. After careful evaluation, 35 studies were included that met the inclusion criteria ( 8 , 29 , 30 , 33 , 36 , 39 , 41 , 45 , 47 , 48 , 51 – 54 , 57 , 59 , 63 , 65 , 66 , 68 , 69 , 71 , 72 , 74 85 ). The detailed flow chart is presented in Supplementary Figure 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the percentage reductions in EDSS score in groups receiving PLEX on days ≤ 15 and days 16 to 30 were significantly greater than those in the groups treated on days 31 to 60 and days 61 to 90 (all, P < 0.05) [ 40 ]. Although two large retrospective studies in adults [ 22 •, 41 ] and one small retrospective study in children with MOG-Ab and ON [ 42 ] demonstrated favorable visual outcome, patients with MOG-Ab can manifest with severe visual loss and permanent paresis or ataxia [ 43 ]. A more aggressive, treatment-resistant, disease course may be seen in younger children in view of the increase susceptibility of the myelinating brain to MOG-Ab disease, as the autoantibody-mediated damage to the not fully matured (uncompact myelin) may result in secondary damage and irreversible axonal loss [ 44 ].…”
Section: Part 4: How To Treat?mentioning
confidence: 99%
“…Atrophy of the brain (in particular the thalami) and spinal cord, measured longitudinally, correlates with disability accumulation and cognition, and could be used as a quantitive outcome measure both clinically and as part of clinical trials . Similarly, optical coherence tomography can be used alongside clinical parameters as an objective measure of neuroaxonal loss in children with optic neuritis …”
Section: Future Perspectives and Areas Of Researchmentioning
confidence: 99%
“…79 Similarly, optical coherence tomography can be used alongside clinical parameters as an objective measure of neuroaxonal loss in children with optic neuritis. 80 Another important area of development is that of induction versus escalation therapy. 81 The current approach to treatment of paediatric-onset multiple sclerosis involves initiation of treatment with safer but probably less-efficacious first-line therapies, then subsequently proceeding to more-efficacious second-line therapies as required ('escalation').…”
Section: Future Perspectives and Areas Of Researchmentioning
confidence: 99%